Exploring spousal disparities: Age, earnings, and education as predictors of intimate partner violence in 29 developing countries - Rafi Amir-ud-Din; Rubina Idrees; Javaria Farooqui; Abdus Sattar Abbasi (Women's Health)
Background: Intimate partner violence (IPV) is widespread and is influenced by individual-specific factors. However, the impact of spousal sociodemographic disparities (age, earnings, education) remains understudied. Objectives: This study investigates the relationship between spousal sociodemographic disparities and women’s IPV experiences in 29 developing countries in South Asia, Sub-Saharan Africa, and the Middle East and North Africa. Design: We used a cross-sectional design, analyzing data from the Integrated Public Use Microdata Series-Demographic and Health Surveys (IPUMS-DHS). Methods: We conducted logistic regression to assess associations between spousal disparities and four forms of IPV including less severe physical violence (LSPV), severe physical violence (SPV), emotional violence (EV), and sexual violence (SV) based on spousal age, earnings, and education disparities. Results: The analysis revealed that spousal education disparities are significantly associated with increased IPV odds. Women with more educated husbands faced higher odds of LSPV (OR = 1.044, 95% CI = 1.01, 1.08; p  < 0.05) and SV (OR = 1.085, 95% CI = 1.04, 1.14; p  < 0.01), with no significant association for SPV or EV. Larger spousal age gaps were consistently associated with a reduced probability of all IPV forms, particularly LSPV (OR = 0.765, 95% CI = 0.72, 0.81; p  < 0.001) and SV (OR = 0.656, 95% CI = 0.58, 0.74; p  < 0.001). Earnings disparities also played a crucial role: women earning more than their husbands faced higher odds of LSPV (OR = 1.361, 95% CI = 1.23, 1.50; p  < 0.001), EV (OR = 1.573, 95% CI = 1.42, 1.74; p  < 0.001), and SV (OR = 1.624, 95% CI = 1.42, 1.86; p  < 0.001). When husbands earned more, women also faced higher odds of IPV, although these associations were weaker. Conclusion: The findings underscore the need for targeted policies to prevent IPV, particularly in low- and middle-income countries, by addressing spousal disparities in age, earnings, and education to promote gender equality.